Caesarean delivery: rate, indications and pregnancy outcome at Suntreso government hospital; an analytical cross-sectional study - Amponsah-Tabi, Seth; Ofori, Helen Achiaa; Boadu, Eric A.; Agyarko-Poku, Thomas; Kekertsor, Martin Yao; Appiah-Denkyira, Kwame Amissah (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Introduction: Globally, caesarean section (CS) rates are increasing, revealing disparities across regions and socioeconomic groups, becoming a challenge due to its overuse or underuse with direct consequences on maternal and neonatal health. Despite this, the factors contributing to these trends and disparities remain insufficiently documented. This study determined the rate, associated indications and maternal and neonatal outcomes of caesarean section deliveries at the Suntreso Government Hospital, Ghana. Methods: This retrospective study encompassed the entire number of women who gave birth within the study time period spanning from 1st January, 2021 to 31st December, 2021. Results: Caesarean section rate over the study period was 33.1%. Previous caesarean section, fetal distress and severe oligohydramnios were the 3 commonest indications for CS. There were 13 adverse maternal outcomes. Maternal deaths after CS were 2 out of 1057 cases. About 91% of patients stayed in the hospital for longer than three days post-surgery. 41% of babies delivered were admitted to the Neonatal Intensive Care Unit (NICU) for various reasons. Pre-eclampsia/eclampsia, antepartum hemorrhage and fetal distress were some indications of caesarean section with significant association with adverse maternal and neonatal outcome. Conclusion: Caesarean section rates were higher than the WHO standard. A repeat CS delivery was the commonest indication. CS should be performed when clinicians anticipate a better outcome for both mother and neonate.